2020
DOI: 10.1097/mph.0000000000001756
|View full text |Cite
|
Sign up to set email alerts
|

Use of Infliximab in the Treatment of Macrophage Activation Syndrome Complicating Kawasaki Disease

Abstract: Kawasaki disease (KD) is an acute systemic vasculitis of unknown etiology. KD can be complicated with macrophage activation syndrome. The optimal treatment for this KD complication has not been established, and a variety of treatments have been used. Infliximab, a chimeric monoclonal antibody that binds tumor necrosis factor, has proved to be efficacious in IV gammaglobulin resistant KD. We present 2 cases of KD complicated with macrophage activation syndrome, including 1 patient with DiGeorge syndrome success… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 40 publications
0
1
0
Order By: Relevance
“…IFX, a recombinant humanized monoclonal antibody against TNF-α, is now approved for use in several immune-mediated disorders, including psoriasis, RA, IBD, ankylosing spondylitis, and IVIG resistant KD (74)(75)(76)(77). Numerous studies have reported that combined treatment with IFX was related to clinical and biochemical improvement in KD complicated with MAS (78). Considering the potential similar pathophysiology between KD complicated with MAS and MIS-C, which is also potentially related to CRS to a certain extent, IFX may play a vital role in CRS with COVID-19.…”
Section: Potential Of Tnf-α Inhibitors In Covid-19mentioning
confidence: 99%
“…IFX, a recombinant humanized monoclonal antibody against TNF-α, is now approved for use in several immune-mediated disorders, including psoriasis, RA, IBD, ankylosing spondylitis, and IVIG resistant KD (74)(75)(76)(77). Numerous studies have reported that combined treatment with IFX was related to clinical and biochemical improvement in KD complicated with MAS (78). Considering the potential similar pathophysiology between KD complicated with MAS and MIS-C, which is also potentially related to CRS to a certain extent, IFX may play a vital role in CRS with COVID-19.…”
Section: Potential Of Tnf-α Inhibitors In Covid-19mentioning
confidence: 99%